Social work practice with people with dementia - Scourfield, Peter (Student social work, 2023)
Social Work Practice with People with Dementia critically discusses the cultural and discursive contexts in which social work with dementia takes place. Social Work Practice with People with Dementia will be of particular interest to social work students and early career social workers, primarily in a UK context. However, it contains much relevant information about dementia and dementia practice for anyone involved with adult health and social care both in the UK and around the world"--